THE NEONATAL OUTCOME IN INFANT BORN TO GESTATIONAL AND PRE-GESTATIONAL DIABETIC MOTHERS (Iraqi Journal of Medical Sciences, 2017)
Background: Diabetes is the 2nd commonest medical complication of pregnancy after hypertension. Infants of diabetic mothers are those infants born to a mother who suffers from diabetes mellitus, but the term refers especially to infants born to a mother who has persistently elevated blood sugar during pregnancy.Objective: To study the complications in infants of diabetic mothers and the difference in the complications between infants of gestational and pre-gestational diabetic mothers.Methods: A cross sectional observational study carried out on (100) neonates of diabetic mothers that delivered in Al-Imamein Al-Kadhimein Medical City; the data was collected between 1st of September 2015 to 1st of December 2015. Maternal history was taken about type of diabetes and babies were divided into 2 groups; 1st group was infants of pregestational diabetic mothers and 2nd group was infants of gestational diabetic mothers. Thorough physical examination of these infants at birth at the neonatal care unit was done. Laboratory investigations included blood sugar, serum calcium, hematocrit, total serum bilirubin and echocardiograph was done in all babies but chest x-ray, abdominal ultrasound, brain ultrasound and electrocardiogram were done whenever indicated.Results: The 1st group (36 cases) 36% of infants was product of mothers having pregestational diabetes and the 2nd group (64 cases) 64% infants of gestational diabetic mothers. Mothers were delivered by cesarean section in 69%. Mothers were primigravida in 31%. Female 59% to male ratio 1.4:1. Hypoglycemia at birth was documented in 39% of cases, was nearly equal in both groups (20%, 19%) respectively. Hypocalcemia in 18%, was more in infants of pregestational diabetic mothers (11% and 7%) respectively. Respiratory complications were the most prominent complications 41 % nearly equal in both groups (22% and 19%) respectively. Macrosomia seen in 23%, more in infants of gestational diabetic mothers (7% and 16%) respectively. Forty % of infants of both group have been discharged in the first 24 hours.Conclusion: The respiratory complications were the most prominent followed by hypoglycemia that occurred mainly to infants of pregestational diabetic mothers. There are statistical differences in infants of pregestational diabetic mothers regarding hypoglycemia, hypocalcemia and respiratory complications. Macrosomia is more in infants of gestational diabetic mothers.Keywords: Neonate, infants, gestational, pregestational diabetes. Citation: Kadhum DE, Abbas SS, Khalaf DK. The neonatal outcome in infant born to gestational and pre-gestational diabetic mothers. Iraqi JMS. 2017; Vol. 15(3): 268-274. doi: 10.22578/IJMS.15.3.8
Keywords: Neonate; infants; gestational; pregestational diabetes